2008
DOI: 10.17221/374-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Embryo recovery from the oviduct in superovulated ewes: a method to improve MOET systems

Abstract: ABSTRACT:The efficiency of embryo recovery in a superovulatory treatment was studied by perfusing the oviduct or the uterine horn in 3.5 and 7 days after sponge withdrawal, respectively. Eighty-four and seventy ewes of Aragonesa breed were used as embryo donors and receptors, respectively. The donors were distributed in 3 replications. The oestrus was synchronized with the insertion of FGA intravaginal sponges (30 mg) for 13 days. Six intramuscular injections of 18 mg pFSH were applied in decreasing doses at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In addition, estrus detection in wild females can generate stress just before the moment of ovulation., We therefore decided to use a natural approach, only introducing the aoudad male with proven fertility, and to monitor the copulation behavior. We had a low embryo recovery rate in comparison with the same procedure in domestic ewes [12], which can be attributed to the low level of fertilization in vivo rather than a failure of the technique, because our procedure has an embryo recovery of more than 85% in domestic ewes when it is performed by the same surgeon [12]. Such sub-optimal fertilization can occur in domestic ewes due to changes in the cervical mucus that generate a deficient sperm transport; this difficulty can be avoided using intrauterine insemination [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, estrus detection in wild females can generate stress just before the moment of ovulation., We therefore decided to use a natural approach, only introducing the aoudad male with proven fertility, and to monitor the copulation behavior. We had a low embryo recovery rate in comparison with the same procedure in domestic ewes [12], which can be attributed to the low level of fertilization in vivo rather than a failure of the technique, because our procedure has an embryo recovery of more than 85% in domestic ewes when it is performed by the same surgeon [12]. Such sub-optimal fertilization can occur in domestic ewes due to changes in the cervical mucus that generate a deficient sperm transport; this difficulty can be avoided using intrauterine insemination [18].…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the embryo collection, ovarian status was evaluated by endoscopy to determine whether surgery was necessary. The mini-laparotomy for the embryo collection was performed according to the technique described by Ramon-Ugalde et al [12]. The flushing medium used was TCM-199 with Hank's Salts containing L-glutamine, HEPES 25 mM (Gibco®, cat.…”
Section: Embryo Collectionmentioning
confidence: 99%
“…The embryo recovery percentage throughout this experiment ranged from 10-30 percent with an average of 21.79 percent, which is quite lower than the usual rates obtained under the traditional decreasing dose FSH protocols (D'Alessandro et al, 1996) [14] . Forcada et al (2012) [18] observed 50-60% recovery rate while Ramon-Ugalde et al (2008) [47] observed 70% recovery rate after uterus flusing in superovulated ewes. Very low recovery rate was observed by López-Saucedo et al (2013) [35] in wild Barbery sheep of Mexico.…”
Section: Recovery Of Embryomentioning
confidence: 98%